Analisisis Perbuatan Melawan Hukum Oleh Kreditur Atas Pembatalan Sepihak Pembayaran Debitur: Studi Putusan Tingkat Pertama, Banding, Dan Kasasi: Analisisis Perbuatan Melawan Hukum Oleh Kreditur Atas Pembatalan Sepihak Pembayaran Debitur: Studi Putusan Tingkat Pertama, Banding, Dan Kasasi - Yasmin, Putri Nabila Yasmin; Arif Pratama, Rio (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
This research is motivated by a legal dispute between a debtor and a creditor due to unilateral cancellation in a credit agreement, which resulted in different rulings at the District Court, High Court, and Supreme Court levels. The study aims to analyze the judges’ considerations and the legal consequences arising from these three decisions. The method used is normative juridical research with a case approach, by analyzing relevant legislation and court decisions. The results indicate that the District Court and High Court considered the creditor’s actions as unlawful due to the absence of good faith, thus ordering the return of collateral and the payment of compensation. Conversely, the Supreme Court annulled those decisions and affirmed that the credit agreement remains binding as long as the debt has not been fully paid, thereby ruling out any unlawful act. In conclusion, there is a contrast between the substantive justice approach adopted by the lower courts and the legal formalism approach applied by the Supreme Court. The implication of this research highlights the importance of harmonizing legal interpretations to ensure legal certainty and protect the rights of parties in credit agreements.